Assessing the Digital Readiness of Tourism Actors in Dompu Regency for Artificial Intelligence–Based Marketing Transformation - Suhaety, Yeye; Mansyuri, M. Ikhwan (Universitas KH. Abdul Chalim Mojokerto, 2026)
Digital transformation driven by Artificial Intelligence (AI) has become a key factor in the development of global tourism. However, the digital readiness of tourism actors in developing regions such as Dompu Regency is still limited. This study aims to analyze the level of digital readiness of tourism actors, identify barriers, and explore opportunities for implementing AI technology in tourism marketing. A qualitative approach with an exploratory case study design is used in this research. Data were collected through in-depth interviews with 13 informants, including MSME actors, homestay owners, tour operators, local government officials, and MSME/digitalization facilitators. Observations and documentation were also carried out to strengthen the findings. Data analysis used a thematic method to identify emerging patterns, themes, and meanings. The findings indicate that the digital literacy of tourism actors is still low; the main obstacles lie in limited internet infrastructure and costs; government support is relatively limited; and understanding of AI is still minimal. However, there is enthusiasm and positive hope for the application of AI technology in the future, especially in aspects of automated promotion and digital reservations. The recommendations of this study emphasize the need for continuous training programs, improvement of internet infrastructure, and collaboration between the government, MSME actors, and digitalization facilitators.